Solvent-free Enzymatic Synthesis of Decyl Acetate: the Cherry on Top? - M. V. Oliveira (2009)
This article presents the results of a building inspection, diagnosis and intervention applied to a significant group of rural houses located in a council at the interior centre of Portugal. The houses external conditions, structural conditions and other aspects related to occupation and use were evaluated by this method. It indicates the necessity of immediate or posterior intervention, on each house, based on a graduate list of the state of conservation of all houses. This inspection methodology has the objective to provide the necessary elements for base intervention options in the rehabilitation to accomplish. The methodology is discussed and proposals for future development are presented.